A review of packed red cell transfusions in the neonatal unit at Charlotte Maxeke Johannesburg Academic hospital - Song Xiaojun (My University, 2017)
Background: Packed red cell transfusion (PRT) is a common therapeutic option in neonates with anaemia. Objectives: The aim of this study is to review the use of PRT in the neonatal unit, and identify any associations with specific complications. Methods: This is a retrospective descriptive study of all neonates who were admitted to the neonatal unit of Charlotte Maxeke Johannesburg Academic Hospital, younger than 72 hours, from 1 January 2013- 31 December 2014. Neonates older than 72 hours, or with missing data, were excluded from the study. The timing and number of transfusions given to each neonate could not be established with the available data and were therefore not included in this study. Neonates were divided according to weight into 2 groups, those weighing less than 1500g, and those 1500g or larger. Within the groups, neonates who were not transfused were compared with babies who were transfused. By means of univariate and multivariate analysis, the characteristics of the neonates and the incidence of complications were reported. Results: The study sample included 3432 neonates. Of these, 2395 were ?:1500g and 1037 neonates were< 1500g. The total number of PRT was 435/3432 neonates ( 12. 7% ). The incidence of necrotizing enterocolitis (NEC) in the smaller transfused group was 11.9% versus 4.6% in the smaller non-transfused (P<0.001). The incidence of NEC in the larger transfused group was 14.1 % versus 0.7% larger non-transfused group (P<0.001). The incidence of late-onset sepsis (LOS) in the smaller transfused group was 49.4% versus 12.0% in the smaller non-transfused group (P<0.001). The incidence of LOS was 3 7.3 % in the larger transfused group versus 2. 8% in the larger non-transfused group (P<0.001). The incidence of bronchopulmonary dysplasia (BPD) in the smaller transfused group was 50.2% versus 5.5% in the smaller non-transfused group (P<0.001 ). The incidence of BPD larger transfused group was 21.2% in the group transfused versus 0.5% in the larger non-transfused group (P<0.001). The incidence of intraventricular hemorrhage (IVH) in the smaller transfused group was 22.0% versus 6.1 % small non-transfused group (p<0.001 ). The incidence of IVH in the larger transfused group was 7.0% versus 0.2% in the larger non-transfused group (p<0.001 ). The incidence of ROP in the smaller transfused group was 9.8% versus 2.0% in the smaller non-transfused group (p<0.001 ). The incidence of conventional mechanical ventilation (CMV) in the smaller transfused group was 40.8% versus 9.1% in the smaller non-transfused group (p<0.001). The incidence of CMV in the the larger transfused group was 60.6% versus 8.0% in the larger non-transfused group. The lengths of stay as well as the duration of CMV in the transfused group were more than double the duration of those who were not transfused. In both groups, after multivariate regression analysis, a significant association was found between PRT and CMV, LOS, BPD, IVH, and birth weight. NEC and ROP were no longer significantly associated with PRTs. Conclusion: 12.7% of neonates admitted to the CMJAH neonatal unit received a PRT. However, the exact timing and number of PRT per neonate were not known. Very low birth weight neonates are 8 times more likely to be transfused compared to larger babies. Future prospective studies are needed to determine whether PR T cause LOS, BPD, IVH, and longer duration of CMV; and also to determine that NEC is not associated with PRT.